CHARACTERIZATION OF SURFACE OF THE (010) FACE OF BORAX CRYSTALS USING EX SITU ATOMIC FORCE MICROSCOPY (AFM): - Suharso Suharso (Universitas Gadjah Mada, 2005)
The surface topology of borax crystals grown at a relative supersaturation of 0.21 has been investigated using ex situ atomic force microscopy (AFM). It was found that the cleavage of borax crystals along the (010) face planes has features of the cleavage of layered compounds, exhibiting cleavage steps of low heights. The step heights of the cleavage of the (010) face of borax crystal are from one unit cell to three unit cells of this face.